Analysis of Arabic Writing Ability Using the Scamper Method for Students - Muslim; Prayoga Saputra; Laily Fitriani; Abdul Aziz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is motivated by the need to gain a deeper understanding of the application of the SCAMPER method in Arabic creative writing among students. The qualitative method is used with three stages, namely data reduction, data display, and conclusions. In the learning context, the lecturer explains the SCAMPER stages before giving the topic to students. The aim of this research is to provide additional insight into the use of SCAMPER in increasing Arabic writing creativity. This research methodology adopts a qualitative survey model approach with a cross-sectional design. Researchers used a questionnaire distributed to 25 MPI students via Google Form after they took part in learning using the SCAMPER method. The survey results were analyzed to diagnose student attitudes, beliefs, or practices regarding the use of SCAMPER in Arabic writing. Research findings show that the use of SCAMPER has a significant positive impact in increasing enthusiasm for learning, understanding of the material, and Arabic writing skills among MPI students. Although most respondents did not have a complete understanding of SCAMPER beforehand, the survey results showed a high level of willingness to adopt this method in their learning. Further efforts are needed to provide a deeper understanding of the use of SCAMPER in improving Arabic writing skills. Therefore, there is a good opportunity to introduce and integrate SCAMPER into the curriculum to improve Arabic writing skills among MPI STAI Al-Hikam students.